1979
DOI: 10.1093/nar/6.4.1387
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin and core particles formed from the inner histones and synthetic polydeoxyribonucleotides of defined sequence

Abstract: Chicken erythrocyte inner histones (H2A, H2B, H3 and H4) were associated with the two complementary homopolymeric polydeoxyribonucleotides and the two alternating copolymeric polydeoxyribonucleotides. No evidence for formation of chromatin-like structures was obtained for the complexes with poly(dG) . poly(dC) or poly(dA) . poly(dT). Both poly (dGdC) . poly(dGdC) and poly(dAdT) . poly(dAdT) could be folded by histones to yield material digested by DNAase I to multiples of about 10 and by staphylococcal nucleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(115 citation statements)
references
References 31 publications
5
109
1
Order By: Relevance
“…The difference in rates of release of 3H and 14C observed in Fig. 2A (51)(52)(53). These results differ slightly from previous studies which indicated that, in a different buffer, rDNA and bulk DNA in isolated nuclei were digested at the same rate by staphylococcal nuclease (10).…”
Section: Resultscontrasting
confidence: 82%
“…The difference in rates of release of 3H and 14C observed in Fig. 2A (51)(52)(53). These results differ slightly from previous studies which indicated that, in a different buffer, rDNA and bulk DNA in isolated nuclei were digested at the same rate by staphylococcal nuclease (10).…”
Section: Resultscontrasting
confidence: 82%
“…The bendability of (AT)n repeats is in fact well known from experiment [12]. Also, protein-induced bending at TATA sequences seems to be especially pronounced [13][14][15][16][17]. The lowest bendability value, on the other hand, is associated with poly(dA) motifs, which is also in agreement with experimental data, obtained by nucleosome studies [9,17] and X-ray crystallography [20,21].…”
Section: Asymmetric Bendability Reflects Propensity To Curvaturesupporting
confidence: 85%
“…It has been known for some time that in vitro nucleosomes have a high preference for certain DNA sequences (11)(12)(13)(14) and tend to avoid other sequences (15)(16)(17)(18)(19)(20)(21)(22). For instance, Kaplan et al (23) concluded from genome-scale nucleosome mapping that intrinsic nucleosome sequence preferences have a dominant role in determining nucleosome organization in vivo.…”
mentioning
confidence: 99%